THE LOCATION BEHAVIOR OF CALL CENTRE FIRMS IN TURKEY - Ebru Seçkin (European Regional Science Association (ERSA), 2011)
Advances in information and communication technologies bring along changes in working and employment conditions. Automationed work is moved to distant areas and businesses get elaborate, far from the center and network-based. Another change similar to the disintegration of production process is also seen in services sector. While jobs to develop technologies are left to the developed regions, routine and demanding jobs are transferred to peripheries. This situation brings about a centre-periphery division in structuring employment. One of the businesses that have emerged in this process is call centers. Firms, operating in various sectors, obtain call center service from outsource firms.Today, call centers are mostly located in less developed regions. While call centers first originated in developed regions, due to the increased costs in these regions, lots of firms have made their call service investments in less developed regions. Labor-intensive call centers are regarded as a solution to the unemployment in less developed regions. Within this framework, cities in Turkey, were evaluated according to location factors that call center firms take into account in this paper. The second part, the discussions in the literature are presented. Factors that become effective location decision of call centre firms were cited. In the third part, cities in Turkey, were evaluated according to location factors that call center firms take into account. Cities that were suitable for call center investment has been determined. In point of view of employees in call centers located in five cities in less developed and developed regions differences was determined by ANOVA and correspondence analysis. In the result, suggestions have been offered for location decision of call center based on statistical factors and employees' point of view
Keywords: 330; labour market; call centre; Turkey; location factors